Impact of Carbon Fiber‐Reinforced Polymer Sheets and Bolt Diameter on the Seismic Performance Enhancement of Steel Beam‐Column Joints - Fayiz Amin; Hafiz Ahmed Waqas; Ijaz Ali; Muhammad Waseem; Muhammad Asif; Khan Abdul Majid; Megersa Kebede Leta (Engineering Reports)
ABSTRACT Beam‐column joints are pivotal for ensuring the resilience of prefabricated steel structures under various loading conditions. Following the major earthquakes of the 1990s, semi‐rigid bolted connections emerged as a promising alternative to traditional welded connections. This study investigates a fully prefabricated Intermediate Beam‐Column Joint (IBCJ) with extended endplates, renowned for its excellent seismic resistance. While significant progress has been made in existing research, there is still a need to thoroughly examine the tension capacity of IBCJs concerning bolt size and explore the potential of Carbon Fiber‐Reinforced Polymer (CFRP) sheets to enhance joint performance under seismic loading. Using the finite element method, this research evaluates the performance of IBCJ under both monotonic and cyclic loading conditions. After validation with experimental data, the study examines various bolt diameters to assess their tension capacity, ductility ratio, secant stiffness, and energy dissipation capacity. The findings indicate that larger bolts exhibit higher ultimate capacities and reduced deformation at failure. Additionally, the study investigates the optimal placement and configuration of CFRP sheets, identifying the backside of the endplates as the most effective location. The application of CFRP significantly enhances bolt tension capacity by up to 1.2 to 1.3 times, demonstrating its potential in reducing bolt failure risk and improving structural reliability under seismic conditions. The superior performance of CFRP‐strengthened bolts can play a crucial role in the design and retrofitting of prefabricated steel structures, potentially contributing to the improvement of existing standards and practices of seismic enhancement of IBCJ.